Desain Jaringan Irigasi Mikro Jenis Mini Sprinkler (Kasus di Laboratorium Outdoor Balai Irigasi) - Dadang Ridwan; Alfi Bagus Prasetyo; Marasi Deon Joubert (Jurnal Irigasi, 2014)
Increasing of land use changing causes more limited agricultural land. Micro irrigation is one of the solutions to increase agricultural productivity on a limited land. This study aims to design a micro irrigation system using mini-sprinkler in limited area of outdoor laboratory in Experimental Station of Irrigation, Bekasi. The plant will be cultivated is tomato. The results of design calculations obtained micro sprinkler type that will be used is HADAR 7110 Inverted Rotor as much as 12 units, wetting diameter of 10,2 m, the distance between the lateral and sprinkler 5 m x 5 m. Irrigation water requirement is 26,25 mm/ application. Time of the maximum irrigation is 5,13 hours, with the maximum irrigation interval is 5 days. Total dynamic head (TDH) required is 28,66 m. Considering to fulfillment greater requirement, the selected pump will be has a 0,25 KW BHP, discharge 1,25 liter/second, with total head of 60 m.. Schedule of irrigation water supply is designed based on the needs of water per growth period between 2,22 to 5,07 hours with an interval of 3-5 days.